Entrepreneurial Expansion and Strategic Feasibility of Foreign Franchises: Evaluating Market Dynamics and Sustainable Growth in Indonesia - Prasetyo Wimar; Endang Sungkawati (Revenue Journal: Management and Entrepreneurship, 2026)
Background: In the era of globalized markets, foreign franchise networks must strategically align their operational models with domestic market dynamics to secure sustainable growth and consumer retention. Objective: This study aims to analyze the strategic adaptation, market feasibility, and consumer behavior alignment of foreign franchise businesses expanding into the Indonesian market. Method: Adopting a systematic qualitative synthesis under a strategic management framework, this research evaluates ten distinct foreign franchise case studies over the 2020–2025 period, focusing on their structural approaches, business strategy execution, and regulatory compliance. Results: The synthesis reveals two dominant operational paradigms: corporate-normative compliance and descriptive-qualitative adaptation. Successful foreign brands achieve a sustainable competitive advantage primarily by reframing their marketing frameworks to fit local consumer preferences and cultural dynamics, alongside establishing resilient contractual risk management. Furthermore, the franchise model proves to be a highly effective vehicle for entrepreneurial expansion when backed by strategic agility. Conclusion: To prevent market switching and optimize local market shares, foreign franchisors must prioritize contemporary brand integration and robust strategic feasibility studies. Future research should leverage advanced empirical metrics to measure the quantitative macroeconomic impacts of these franchise ecosystems on the Indonesian entrepreneurial landscape.